Case study project notes on the hydrodynamic and morphologic effects on hydraulic structure. (January 2021) - Kuntjoro,; Bayuaji, Ridho; Tatas,; Khoiri, Mokh
Highlights: An evaluation of gas pipe protective building at oblique position accross the river bend with dynamic flow debit contained sand sediment up to boulder. All components of the substitute building shall work simultaneously and they are quite reliable as proven by the good physical condition of the building once the construction is completed and the flood occurred. Abstract: It is started from an evaluation of gas pipe protective building at oblique position accross the river bend with high discharge and dynamic flow contained trees, sand sediment, gravels up to boulder. The results of the failure analysis and evaluation on the previous building as follows: The structure is located on incorrect installation it is in oblique position exactly on the sharp curve of the river. The building is in such an alarming condition for the sub grade is eroded, saddle weight and anchor do not work properly due to erosion, upper flow and seepage flow. Gabions do not work properly they are tilted and lifted by the washed away by flood with its drift material. Due to the oblique position accross the river bend, an additional construction will be necessary. This gas pipe requires a protective building to return it to its former condition that is buried in two meters deep. Therefore, a check dam construction is required. Due to the oblique position accross the river bend, an additional construction will be necessary as crib that will direct the flow with such combination of cribs and check dam. The aim and goal of gas pipe protection can be achieved, accordingly. The results of gas pipe protective building evaluation are as follows: All components of the substitute building shall work simultaneously and they are quite reliable as proven by the good physical condition until the building construction is completed and once flood occured. After ones time flooding, the structure stability remains in good condition, does not break, does not slide, and does not roll. The sedimentation is seen at the upstream of the cribs during the construction of main building and afterwards. The main building works properly as required and it is proven by sedimentation that already occurs at the upstream of the check dam.